Construction and validation of the Wingate index model for elite athletes - Wang, J.; Zong, Y. (Heliyon, 2024)
Objective The gold standard for measuring anaerobic fitness is the power cycle ergometer test, but this method is expensive and time-consuming, and it has negative effects on pre-competition performance. This study aims to utilize the strong correlation between accessible body composition indices and less accessible anaerobic power bicycle indices to establish and verify a Wingate Index Model.